EGFR pathway subgroups in Chilean colorectal cancer patients, detected by mutational and expression profiles, associated to different clinicopathological features - Karin Alvarez; Paulina Orellana; Cynthia Villarroel; Luis Contreras; Hiroshi Kawachi; Maki Kobayashi; Ana Maria Wielandt; Marjorie De la Fuente; Juan Carlos Triviño; Udo Kronberg; Pilar Carvallo; Francisco López-Köstner (Tumor Biology)
Colorectal cancer is a multistep process affecting several signaling pathways including EGFR (epidermal growth factor receptor), a therapeutic target for metastatic disease. Our aim was to characterize the mutational and expression profiles of the EGFR pathway in colorectal tumors and to integrate these results according to five previously defined groups. We screened seven genes for mutations ( KRAS-BRAF-PIK3CA-PIK3R1-AKT1-MAP2K1-PTEN ) and six proteins (EGFR-p110α-p85α-PTEN-phosphoAKT-phosphoMEK1) by immunohistochemistry, PTEN deletion, and MSI. At least one mutated gene was observed in 68% of tumors ( KRAS 45%, PIK3CA 21%, BRAF 14%, and PTEN 7%). PTEN deletion was observed in 10.7% of tumors and 19.6% were MSI-High. In all, 54% of tumors showed a high EGFR expression, 48% p110α, 4.4% phosphoAKT, and 22% phosphoMEK1; and 43% showed low PTEN expression and 22% p85α. In total, five groups of tumors were defined based on MSI, BRAF , and KRAS mutations. Three groups gather mainly early-stage tumors, whereas a fourth group is mostly conformed by advanced tumors. We described here that 71.4% of tumors from one group have a mutated PI3K/PTEN pathway, in comparison to other groups having 32%, 27%, and 25%. In addition, the five groups are differentiated by molecular features such as EGFR, p85α, p110α, and PTEN, showing variable expression among tumor groups. In conclusion, alterations on the EGFR pathway were found in a high percentage of colorectal cancer patients. Using the integration of diverse molecular markers, we ratified previous classification in an ethnic group having relevant genetic differences and living in a different environmental background, adding complementary molecular targets related to therapy.